Development of liveworksheet-based interactive LKPD on the biodiversity material of class X - Elsi Susilawati; Ainul Uyuni Taufiq; Ummul Hasanah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The use of teaching materials with conventional-based student worksheets (LKPD) still dominates, while accessing the internet is easy and facilitates learning. The facilities and infrastructure owned are also very supportive in the application process, so there is a need for developing research that encourages students to be active in learning using the internet with a more enjoyable experience. This research aims to develop valid, practical, and effective Liveworksheet-based interactive LKPD using the ADDIE development model. The research instruments used were validation questionnaires, response questionnaires, learning achievement tests, and observation sheets. The subjects in this study were students of class X MIA 3 (29 students). The results show that Liveworksheet-based interactive LKPD have a very valid with an average value of 3.6. The practicality level based on the results of the student response questionnaire was 82.1%, and the teacher's response value was 89.2%. The level of effectiveness obtained by very good criteria based on the completeness of the classical learning outcomes is 100%. The developed Liveworksheet-based interactive LKPD meet the valid, practical, and effective criteria. Liveworksheet-based interactive LKPD provides an enjoyable experience for students and achieves classical mastery.Abstrak Penggunaan bahan ajar dengan lembar kerja peserta didik (LKPD) yang berbasis konvensional masih mendominasi, sementara mengakses internet sudah mudah dan dapat memudahkan proses pembelajaran. Sarana dan prasarana yang dimiliki juga sangat mendukung dalam proses pengaplikasiannya, sehingga perlu penelitian pengembangan yang mendorong peserta didik aktif dalam pembelajaran menggunakan internet dengan pengalaman yang lebih menyenangkan. Tujuan penelitian ini adalah mengembangkan LKPD interaktif berbasis Liveworksheet yang valid, praktis, dan efektif menggunakan model pengembangan ADDIE. Instrumen penelitian yang digunakan adalah angket validasi, angket respon, tes hasil belajar, dan lembar observasi. Adapun subjek pada penelitian ini adalah peserta didik kelas X MIA 3 (29 peserta didik). Hasilnya menunjukkan LKPD interaktif berbasis Liveworksheet memiliki tingkat kevalidan sangat valid dengan nilai rata-rata 3,6. Tingkat kepraktisan berdasarkan hasil angket respon siswa yaitu 82.1% dan nilai respon guru adalah 89.2%. Tingkat keefektifannya diperoleh kriteria sangat baik berdasarkan ketuntasan hasil belajar secara klasikal yang diperoleh adalah 100%. Artinya LKPD interaktif berbasis Liveworksheet yang dikembangkan memenuhi kriteria valid, praktis, dan efektif. LKPD interaktif berbasis Liveworksheet memberikan pengalaman yang menyenangkan bagi peserta didik dan mencapai ketuntasan klasikal.